Synthesis and reactivity of azole-based iodazinium salts - Kuczmera, Thomas J.; Dietz, Annalena; Boelke, Andreas; Nachtsheim, Boris J. (Beilstein Journal of Organic Chemistry, 2023)
A systematic investigation of imidazo- and pyrazoloiodazinium salts is presented. Besides a robust synthetic protocol that allowed us to synthesize these novel cyclic iodonium salts in their mono- and dicationic forms, we gained in-depth structural information through single-crystal analysis and demonstrated the ring opening of the heterocycle-bridged iodonium species. For an exclusive set of dicationic imidazoiodaziniums, we show highly delicate post-oxidation functionalizations retaining the hypervalent iodine center.
Keywords: building block; heterocycles; hypervalent compounds; iodonium salts; one-pot synthesis

(untitled) - Yoshimura, A.; Zhdankin, V. V. (Chem. Rev., 2016)

Hypervalent Iodine Chemistry - Wirth, T. (Springer International Publishing, 2016)

(untitled) - Boelke, A.; Finkbeiner, P.; Nachtsheim, B. J. (Beilstein J. Org. Chem., 2018)

(untitled) - Dohi, T.; Kita, Y. (Chem. Commun., 2009)

(untitled) - Moriarty, R. M. (J. Org. Chem., 2005)

(untitled) - Ochiai, M. (Chem. Rec., 2007)

(untitled) - Dohi, T.; Takenaga, N.; Goto, A.; Fujioka, H.; Kita, Y. (J. Org. Chem., 2008)

(untitled) - Mizar, P.; Laverny, A.; El-Sherbini, M.; Farid, U.; Brown, M.; Malmedy, F.; Wirth, T. (Chem. – Eur. J., 2014)

(untitled) - Kürti, L.; Herczegh, P.; Visy, J.; Simonyi, M.; Antus, S.; Pelter, A. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Moriarty, R. M.; Prakash, O.; Duncan, M. P. (J. Chem. Soc., Chem. Commun., 1985)

(untitled) - Phipps, R. J.; Gaunt, M. J. (Science, 2009)

(untitled) - Ghosh, R.; Stridfeldt, E.; Olofsson, B. (Chem. – Eur. J., 2014)

(untitled) - Scattolin, T.; Bortolamiol, E.; Visentin, F.; Palazzolo, S.; Caligiuri, I.; Perin, T.; Canzonieri, V.; Demitri, N.; Rizzolio, F.; Togni, A. (Chem. – Eur. J., 2020)

(untitled) - Grushin, V. V. (Chem. Soc. Rev., 2000)

(untitled) - Chatterjee, N.; Goswami, A. (Eur. J. Org. Chem., 2017)

(untitled) - Collette, J.; McGreer, D.; Crawford, R.; Chubb, F.; Sandin, R. B. (J. Am. Chem. Soc., 1956)

(untitled) - Zhu, D.; Wu, Z.; Liang, L.; Sun, Y.; Luo, B.; Huang, P.; Wen, S. (RSC Adv., 2019)

(untitled) - Jiang, M.; Guo, J.; Liu, B.; Tan, Q.; Xu, B. (Org. Lett., 2019)

(untitled) - Liu, Z.; Zhu, D.; Luo, B.; Zhang, N.; Liu, Q.; Hu, Y.; Pi, R.; Huang, P.; Wen, S. (Org. Lett., 2014)

(untitled) - Zhu, K.; Xu, K.; Fang, Q.; Wang, Y.; Tang, B.; Zhang, F. (ACS Catal., 2019)

(untitled) - Reddy Kandimalla, S.; Prathima Parvathaneni, S.; Sabitha, G.; Subba Reddy, B. V. (Eur. J. Org. Chem., 2019)

(untitled) - Robidas, R.; Reinhard, D.; Huber, S. M.; Legault, C. (ChemPhysChem, 2023)

(untitled) - Heinen, F.; Reinhard, D. L.; Engelage, E.; Huber, S. M. (Angew. Chem., Int. Ed., 2021)

(untitled) - Batsanov, A. S.; Petrov, V. N.; Struchkov, Y. T.; Egorova, L. D.; Lisichkina, I. N.; Tolstaya, T. P. (Bull. Acad. Sci. USSR, Div. Chem. Sci. (Engl. Transl.), 1985)

(untitled) - Tolstaya, T. P.; Egorova, L. D.; Lisichkina, I. N. (Chem. Heterocycl. Compd., 1985)

(untitled) - Boelke, A.; Lork, E.; Nachtsheim, B. J. (Chem. – Eur. J., 2018)

(untitled) - Boelke, A.; Kuczmera, T. J.; Caspers, L. D.; Lork, E.; Nachtsheim, B. J. (Org. Lett., 2020)

(untitled) - Boelke, A.; Nachtsheim, B. J. (Adv. Synth. Catal., 2020)

(untitled) - Boelke, A.; Kuczmera, T. J.; Lork, E.; Nachtsheim, B. J. (Chem. – Eur. J., 2021)

(untitled) - Boelke, A.; Sadat, S.; Lork, E.; Nachtsheim, B. J. (Chem. Commun., 2021)

(untitled) - Kuczmera, T. J.; Boelke, A.; Nachtsheim, B. J. (Eur. J. Org. Chem., 2022)

(untitled) - Damrath, M.; Caspers, L. D.; Duvinage, D.; Nachtsheim, B. J. (Org. Lett., 2022)

(untitled) - Caspers, L. D.; Spils, J.; Damrath, M.; Lork, E.; Nachtsheim, B. J. (J. Org. Chem., 2020)

(untitled) - Guilbault, A.-A.; Basdevant, B.; Wanie, V.; Legault, C. Y. (J. Org. Chem., 2012)

(untitled) - Batsanov, S. S. (Inorg. Mater., 2001)

(untitled) - Heinen, F.; Engelage, E.; Dreger, A.; Weiss, R.; Huber, S. M. (Angew. Chem., Int. Ed., 2018)

(untitled) - Hu, Z.; Tang, Y.; Yu, B. (J. Am. Chem. Soc., 2019)

(untitled) - Wang, M.; Fan, Q.; Jiang, X. (Org. Lett., 2016)

(untitled) - Zhu, D.; Liu, Q.; Luo, B.; Chen, M.; Pi, R.; Huang, P.; Wen, S. (Adv. Synth. Catal., 2013)

(untitled) - Zhu, L.; Guo, P.; Li, G.; Lan, J.; Xie, R.; You, J. (J. Org. Chem., 2007)

(untitled) - Zhu, D.; Chen, M.; Li, M.; Luo, B.; Zhao, Y.; Huang, P.; Xue, F.; Rapposelli, S.; Pi, R.; Wen, S. (Eur. J. Med. Chem., 2013)

(untitled) - Wu, B.; Yoshikai, N. (Angew. Chem., Int. Ed., 2015)

(untitled) - Wonner, P.; Vogel, L.; Düser, M.; Gomes, L.; Kniep, F.; Mallick, B.; Werz, D. B.; Huber, S. M. (Angew. Chem., Int. Ed., 2017)

(untitled) - Lima, H. M.; Lovely, C. J. (Org. Lett., 2011)

(untitled) - Das, R.; Banerjee, M.; Rai, R. K.; Karri, R.; Roy, G. (Org. Biomol. Chem., 2018)

(untitled) - Prasher, P.; Sharma, M. (Drug Dev. Res., 2022)

(untitled) - Aguayo-Ortiz, R.; Cano-González, L.; Castillo, R.; Hernández-Campos, A.; Dominguez, L. (Chem. Biol. Drug Des., 2017)